Medeia vozes de Christa Wolf : a reinvenção polifônica do mito trágico - Wexel, Juliana (My University, 2014)
This dissertation proposes an investigation about the recreation of the greek's myth Medéia in the german novel Medeia Vozes, by Christa Wolf, through the aplication of polyphony's theory by the russian linguist Mikhail Bakhtin. It tries to identify the reinvention of the ancestral myth of the witch Bárbara, who kill her children to revenge the husband betrayal, originally described in the greek tragedy Medéia, by Eurípedes, through analysis of multiple voices's that compose the contemporary book written by the german writer. To realise this study, it was chosen the polyphony's theory like an instrument to be used in the modern narrative analysis, understanding that it would be appropriated to the text exam, because it operates like a way to reinvent the universe of the greek myth and all of its characters, but mainly the one about the betrayed and vindictive woman, who is changed by the contemporary narrative.
A presente dissertação apresenta uma investigação sobre a reinvenção do mito grego de Medéia no romance alemão Medeia Vozes, de Christa Wolf, através da aplicação da teoria da polifonia do linguista russo Mikhail Bakhtin. Busca-se identificar tal reinvenção do mito ancestral da feiticeira bárbara que mata os filhos para vingar-se da traição do marido, originalmente descrito na tragédia grega Medéia de Eurípedes, através da análise das vozes múltiplas que compõem a obra contemporânea da escritora alemã. Para realizar o estudo, escolheu-se a teoria da polifonia como instrumento a ser utilizado no percurso de análise da narrativa moderna por entender-se ser adequada ao exame do texto, pois opera como uma forma de reinventar o universo do mito grego e todas as suas personagens, mas principalmente o da mulher traída e vingativa, que é transformada pela narrativa contemporânea.
Keywords: Medéia (Mitologia grega) na literatura; Teatro grego; Médeia vozes (Obra literária)